Psychosocial correlates of fertility-related quality of life among infertile women with repeated implantation failure: The mediating role of resilience - Ni, Ying; Huang, Limin; Zhang, Enming; Xu, Lianying; Tong, Chenye; Qian, Wen; Zhang, Aijun; Fang, Qiong (Frontiers in Psychiatry, 2022)
Abstract Objective: This study aimed to examine associations between psychosocial factors and fertility-related quality of life (FertiQoL) among infertile women with repeated implantation failure (RIF), and to identify the possible role of resilience in mediating the effect of social support on FertiQoL. Methods: A cross-sectional study was conducted with 234 infertile women with RIF in total. Fertility quality of life scale (FertiQoL), perceived social support scale (PSSS), and Connor-Davidson Resilience Scale (CD-RISC) were used to evaluate the patients. Data were described by univariate and multivariate analyses. Stepwise regression method was performed to analyse the mediating effect of resilience. Results: Social support had a positive predictive effect on FertiQoL (β=0.757, P<0.001), also positive on resilience (β=0.847, P<0.001). After both variables were added to the regression equation, resilience was found to have a significant positive predictive effect on FertiQoL (β=0.798, P<0.001), while the predictive effect of social support on FertiQoL was no longer significant (β=0.081, P>0.05). The results indicated that resilience played a complete mediating role between social support and FertiQoL Conclusion: This study preliminarily verified the mediating role of resilience between social support and FertiQoL among infertile women with RIF. Interventions that consider enhancing resilience and building social support will likely improve their FertiQoL.